Digital government in Peru : working closely with citizens - Organisation for Economic Co-operation and Development (OECD Digital Government Studies, 2019)
This digital government study explores the state of the digitalisation of the public sector in Peru. It addresses recent efforts to build an institutional and legal framework to support the digital transformation of the public sector. It also discusses the design and delivery of, and access to, public services, and the role that digital technologies can play in improving them. Finally, this report assesses the state of data governance and open data in Peru’s public sector.